THE USE OF SIMPLE PRESENT TENSE VERB AND ADJECTIVE IN WRITING DESCRIPTION TEXT - Fauzi Ashari; Syahfitri Purnama (Universitas Indraprasta PGRI, 2019)
Abstract. The aim of the research is to know: 1) mistake which often in writing text descriptive. 2) mistake of usage of tense present simple in writing text descriptive.. 3) mistake of usage of adjective in writing text descriptive student Senior High School in Bekasi. If is true there mistake which is signifikan hence how big mistake of simple tense present and of adjective in writing text descriptive. Method use in this research is an descriptive kualitative. Sampel of the research followed by 65 from 645 student consisting of 33 students class 8 from Junior High School 1 Tarumajaya and 32 student class 8 dan 32 8 from Junior High School 2 Tarumajaya. Data collecting is taken through test which consist of giving of tes write text of deskripsi in English and here in after analyse found by mistake is student in it. End session, 1) There are 232 mistake of tense present simple and of adjective in descriptive article of student, among others 126 mistake of tense present simple and 106 mistake of adjective. 2) Type mistake of using of tense present simple which is often conducted by student is omission of error counted 100 mistake with percentage 79 %. Of Omission Error is mistakes having the character of omission marked by absence item which ought to there in real correct and good sentence. 3) While type mistake of usage of adjective which often conducted by student is Misodering of error counted 47 mistake with percentage 44 %. Of Misodering Error caused by location which not true to morpheme group or morpheme in sentence meaning can be concluded by most of all student do mistake write of simple tense present and almost semi from student mistake write adjective in text of deskriptive.Keywords : Simple present tense, verb, adjective, text description